Pointwise completeness and pointwise degeneracy of fractional standard and descriptor linear continuous-time systems with different fractional orders - Kaczorek, Tadeusz (1932- ); Sajewski, Łukasz (Zielona Góra: Uniwersytet Zielonogórski)
Descriptor and standard linear continuous-time systems with different fractional orders are investigated. Descriptor systems are analyzed making use of the Drazin matrix inverse. Necessary and sufficient conditions for the pointwise completeness and pointwise degeneracy of descriptor continuous-time linear systems with different fractional orders are derived.
Keywords: descriptor systems; fractional systems; noncommensurate order; pointwise completeness; pointwise degeneracy